Optimasi Jadwal Pembelajaran Sekolah menggunakan Metode Hybrid Cat Swarm Optimization (Studi Kasus: SD Muhammadiyah 2 Denpasar) - I Gede Adi Brahman Nugraha; Nurul Hidayat; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Educational Timetable are the main administrative activity for various institutions. In this study, the researcher will concentrate on the problem of school timetabling. School timetabling at SD Muhammadiyah 2 Denpasar is made every new school academic year. In this study, a system was created that can perform school scheduling using the hybrid cat swarm optimization method in optimizing school timetable. The performance of the hybrid cat swarm optimization algorithm, it shows that the average fitness value shows the best results on the number of cats of 10, CSO iterations of 750, and LSRP iterations of 500 with a fitness value of 104,243. Timetabling using system is able to obtain school timetable without any teacher clashes.